1987
DOI: 10.3109/00207458708987111
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mild Maternal Stress During Pregnancy on the Behavior of Rat Pups

Abstract: Mild maternal stress in the form of chronic daily subcutaneous injections of saline or the vehicle for diazepam to pregnant rats was shown to result in some long term, subtle but reliable, changes in the behavior of the offspring. The same vehicle given for the same period of time in the dam's drinking water, without injection had no effect on the development of later behavior of rat pups. Chronic prenatal injections of saline or vehicle for diazepam, used in many experiments as controls for the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…During the next 4 decades, numerous studies documented a wide range of prenatal stress-induced effects on the developing fetus and infant (Field, Sandberg, Quetel, Garcia, & Rosario, 1985;Nuckolls, Cassel, & Kaplan, 1972;Ottinger & Simmons, 1964;Stott, 1959;Ward, 1972;Williamson, LeFevre, & Hector, 1989). In studies with rodents, stress during pregnancy was reported to result in low birth weight and early motor retardation (Fride & Weinstock, 1984), deficits in discrimination learning (Grimm & Frieder, 1987), feminization of the male fetus (Ward, 1972), and increased anxiety under conditions of novelty (Fride, Dan, Gavish, & Weinstock, 1985). These reports concurred with studies on humans linking stressful life events during pregnancy to reductions in infant birth weight and early motor delays (Field et al 1985), increased anxiety (Meijer, 1985), neurological dysfunction, developmental retardation, and behavior disturbances (Stott, 1973).…”
supporting
confidence: 76%
“…During the next 4 decades, numerous studies documented a wide range of prenatal stress-induced effects on the developing fetus and infant (Field, Sandberg, Quetel, Garcia, & Rosario, 1985;Nuckolls, Cassel, & Kaplan, 1972;Ottinger & Simmons, 1964;Stott, 1959;Ward, 1972;Williamson, LeFevre, & Hector, 1989). In studies with rodents, stress during pregnancy was reported to result in low birth weight and early motor retardation (Fride & Weinstock, 1984), deficits in discrimination learning (Grimm & Frieder, 1987), feminization of the male fetus (Ward, 1972), and increased anxiety under conditions of novelty (Fride, Dan, Gavish, & Weinstock, 1985). These reports concurred with studies on humans linking stressful life events during pregnancy to reductions in infant birth weight and early motor delays (Field et al 1985), increased anxiety (Meijer, 1985), neurological dysfunction, developmental retardation, and behavior disturbances (Stott, 1973).…”
supporting
confidence: 76%
“…In addition, PS rats were less willing to leave their cage in the home cage emergence test. Data from both anxietyrelated tests used support the general idea that PS may lead to more anxious offspring [Thompson, 1957;Archer and Blackman, 1971;Grimm and Frieder, 1987;Wakshlak and Weinstock, 1990;Weinstock et al, 1992;Poltyrev et al, 1996;Vallee et al, 1997].…”
Section: Discussionmentioning
confidence: 77%
“…In conditioned avoidance tests, the prenatally stressed rats showed shorter latencies and more avoidance responses than the controls (Joffe, 1965a(Joffe, , 1965b. When tested for brightness discrimination learning in a maze, the prenatally stressed rats learned more slowly than the controls (Grimm & Frieder, 1987). In general, it seems that prenatal stress impairs learning capabilities, but may facilitate learning in fearful situations.…”
Section: Effects Of Prenatal Stress: An Animal Modelmentioning
confidence: 94%
“…Indeed, different types of stressful procedures applied to pregnant rodents are well documented and have been shown to produce numerous biological and behavioral dysfunctions in both dams (Becker & Kowall, 1977;Power & Moore, 1986) and pups (Barlow, Henry, Kabbaj, Simon, Le Moal, & Maccari, 1994;Knight, & Sullivan, 1978;Maccari et al, 1995;Peters, 1988;Politch & Herrenkohl, 1984;Weinstock, 1997). In these different studies, pregnant animals were subjected to cutaneous injections of saline (Grimm & Frieder, 1987), ACTH (Fameli, Kitraki, & Stylianopoulou, 1995), toluene or alcohol inhalation exposure Ogilvie & Rivier, 1997), conditioned avoidance training (Thompson, 1957), immobilization (Rojo, Marin, & MenendezPatterson, 1985), heat and restraint (Politch & Herrenkohl, 1984), sleep deprivation (Suchecki & Palermo Neto, 1991;Velazquez-Moctezuma, Salazar, & Rueda, 1993), hyperthemia (Shiota & Kayamura, 1989), immersion in cold water (Guo et al, 1993), food restriction (Wright, Crawford, & Anderson, 1988) or repeated electric tail shocks (Takahashi & Kalin, 1991). Of these different models, the one employed by Ward (1972) and Ward & Weisz (1984) involving physical constraint in a plastic cylinder under strong light illumination remains the most commonly used (Maccari et al, 1995;Vallée, Mayo, Maccari, Le Moal, & Simon, 1996;Vallée, Mayo, Dellu, Le Moal, Simon, & Maccari, 1997).…”
Section: Effects Of Prenatal Stress: An Animal Modelmentioning
confidence: 99%